Penerapan Unggah-Ungguh Basa dalam Etika Berkomunikasi Menggunakan Bahasa Jawa di Media Sosial - Sulaksono, Djoko; Waluyo, Budi; Rahmat; Tristanti, Rosy; Ayuani, Kusmira Dwi; Lestari, Winda Dwi; Fitriana, Tya Resta (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This community service program aims to introduce and instill the values ​​of etiquette and politeness in Javanese language for communicating on social media. The partner of this activity is SMP Negeri 2 Surakarta. This training targets school students. One of the reasons for holding the training at this school is because this school has a very large number of students with the condition that almost all of the students use cellphones in their daily lives. The event carried out was a training in etiquette and politeness in communicating using Javanese language on social media conducted by the Pengabdian Kepada Masyarakat Hibah Grup Riset (PKM HGR-UNS) Tahun 2025 Program Studi Pendidikan Bahasa Jawa, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sebelas Maret Surakarta. The methods used in this community service activity are: (1) expository (explanation), (2) group discussion, and (3) assignments. The results of the activity show that junior high school students have a better understanding of Javanese language ethics in the digital space, and are able to identify and apply appropriate forms of etiquette and politeness in various online communication situations. This activity demonstrates the effectiveness of a local culture-based educational approach in fostering polite and ethical language awareness among the younger generation. Therefore, local wisdom values, such as polite language, need to be continuously internalized in language education, particularly in the context of today's digital communication.